2017
DOI: 10.1038/srep44479
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating littering, urban runoff and marine transport as sources of marine debris in coastal and estuarine environments

Abstract: Marine debris is a burgeoning global issue with economic, ecological and aesthetic impacts. While there are many studies now addressing this topic, the influence of urbanisation factors such as local population density, stormwater drains and roads on the distribution of coastal litter remains poorly understood. To address this knowledge gap, we carried out standardized surveys at 224 transect surveys at 67 sites in two estuaries and along the open coast in Tasmania, Australia. We explored the relative support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 34 publications
4
51
1
1
Order By: Relevance
“…The site is not subject to large scouring events, thus any deposition is likely to remain in place. In addition, the site is much closer to sewage and stormwater outfall drains, which we found to be sources of plastic pollution in previous work (Willis et al, 2017). This result is similar to those found in other studies, which found higher numbers of plastics at sites closer to storm drain outfalls (Duckett and Repaci, 2015;Horton et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…The site is not subject to large scouring events, thus any deposition is likely to remain in place. In addition, the site is much closer to sewage and stormwater outfall drains, which we found to be sources of plastic pollution in previous work (Willis et al, 2017). This result is similar to those found in other studies, which found higher numbers of plastics at sites closer to storm drain outfalls (Duckett and Repaci, 2015;Horton et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Whether a study from Europe describing how floating macro-plastics from the Rhone reach the Mediterranean (Castro-Jiménez et al, 2019) or research from Indonesia suggesting how rivers transport land-based plastic to the ocean (van Emmerik et al, 2019), the literature is replete with examples. In a comprehensive study testing hypotheses for how debris reaches oceanic systems, Willis et al (2017) find that most debris comes from local sources. The Stemming the Tide report confirms that rivers bring debris from upstream communities to coastal areas (Ocean Conservancy, 2015).…”
Section: Rivers Of Plasticmentioning
confidence: 99%
“…A number of studies argue that rivers and terrestrial waterways facilitate the transport of discarded plastics from land to the ocean (Colton et al, 1974;Sheavly and Register, 2007;Munari et al, 2016;Willis et al, 2017;Crosti et al, 2018). Lebreton et al (2017) estimated that river systems carry between 1.15 and 2.41 million tonnes of plastic litter to coastal and marine environments every year, with around 80% of MPP coming from land-based sources.…”
Section: Sources Pathways and Policy Responsesmentioning
confidence: 99%